DAİRESEL ÇARPAN BİR JETLE SOĞUTMANIN AKIŞ DİNAMİĞİ ETKİLERİNİN DENEYSEL OLARAK İNCELENMESİ - Çelik, Nevin; Kıstak, Celal; Eren, Haydar (Dicle University, 2025)
Bu çalışmada, dairesel çarpan jetin ısı transferi ve akış dinamiği üzerindeki etkileri deneysel olarak incelenmiştir. Çalışmada, jet akımı için çapı d =13.8 mm olan bir alüminyum boru kullanılarak, Reynolds sayısı 5000?25000 aralığında deneyler gerçekleştirilmiştir. Lüle ile çarpma yüzeyi arasındaki mesafe (h/d), farklı değerlerde değiştirilerek (2?10) jetin performansı değerlendirilmiştir. Yerel Nusselt sayıları (Nu), durma noktasındaki Nusselt sayısı (Nu0) ve ortalama Nusselt sayıları (Nuavg) detaylı şekilde analiz edilmiştir. Sonuçlar, h/d mesafesinin ve Reynolds sayısının ısı transferi performansı üzerinde önemli etkileri olduğunu göstermiştir. Artan Reynolds sayısı ve uygun h/d mesafeleri, durma noktasında daha yüksek ısı transferine olanak sağlamıştır. Bu bulgular, çarpan jetlerin enerji verimli soğutma uygulamalarındaki potansiyelini ortaya koymaktadır.

This study experimentally investigates the effects of a circular impinging jet on heat transfer and flow dynamics. Using an aluminum nozzle with a diameter of d=13.8?mm, experiments were conducted within the Reynolds number range of 5000?25000. The nozzle-to-plate distance (h/d) was varied between h/d=2?10 to evaluate the jet's performance. Local Nusselt numbers (Nu), stagnation point Nusselt number (Nu0), and average Nusselt numbers (Nuavg) were analyzed in detail. The results demonstrated that both the nozzle-to-plate distance and Reynolds (Re) number significantly influence heat transfer performance. Increased Reynolds numbers and optimal h/d distances led to enhanced heat transfer at the stagnation point. These findings highlight the potential of impinging jets for energy-efficient cooling applications. The optimal nozzle-to-plate distance for maximum heat transfer was found to be h/d = 6, with a 30.5% increase in Nusselt number at Re = 25000. Additionally, turbulence intensity played a crucial role in heat transfer performance, particularly in the wall jet region, where it enhanced mixing and improved thermal efficiency.
Experimental Investıgation Of Flow Dynamics Effects Of Cooling With A Circular Impınging Jet
Keywords: Mechanical Engineering (Other); Makine Mühendisliği (Diğer)